ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA UKM PADA SEKTOR INDUSTRI PENGOLAHAN MAKANAN DI KOTA SEMARANG - Krisdanti, Gadiza; Rodhiyah, Rodhiyah (Jurnal Ilmu Administrasi Bisnis, 2016)
The number of food processing SMEs in 2014 increased compared to the previous year. Nevertheless, anincreasing number are not necessarily followed by the success of the business. For that, you need toknow what factors are affecting the performance of SMEs. This study aims to determine the influence offactors of food processing performance of SMEs. This type of research is exploratory research. Thesamples used were 62 respondents with saturated sampling technique. The analytical method used isquantitative analysis, consisting of factor analysis, correlation, determination test, simple regression test,t-test, regression test and F-test using SPSS 17.0 for Windows. Discussion of the results showed thecharacteristics of SMEs, the characteristics of the entrepreneur, the entrepreneur psychology, andhuman resources have a medium level of relationship and positive influence on the performance ofSMEs, but only two were significant, namely the characteristics of SMEs and human resources, whilecreativity and innovation does not affect the performance of SMEs. SMEs advised to improve the qualityof marketing, attention to the environment to add to the experience, do not waste the opportunity comes,consistently keep running the business, improve the equipment and the willingness to use newtechnologies.